Drivers of bromeliad leaf and floral bract variation across a latitudinal gradient in the Atlantic Forest. (24th November 2019) - Neves, Beatriz; Zanella, Camila M.; Kessous, Igor M.; Uribbe, Fernando P.; Salgueiro, Fabiano; Bered, Fernanda; Antonelli, Alexandre; Bacon, Christine D.; Costa, Andrea F.
Abstract: Aim: Understanding the complex interaction and relative contributions of factors involved in species and trait diversification is crucial to gain insights into the evolution of Neotropical biodiversity. Here, we investigated the drivers of morphological variation in bromeliads along a latitudinal gradient in a biodiversity hotspot. Location: Atlantic Forest, Brazil. Taxon: A species complex in the genus Vriesea (Bromeliaceae). Methods: We measured shape and size variation for 208 floral bracts and 176 leaves in individuals from 14 localities using geometric morphometrics. We compiled data for two chloroplast regions ( matK and trnL‐F ) from 89 individuals to assess genetic diversity, population structure and phylogenetic relationships. We tested the influence of climate, altitude and genetic distance on morphological traits using linear statistical models. Results: Temperature seasonality is a main driver of floral bract shape. Together with precipitation, it also explains changes in leaf size across the latitudinal gradient. Shifts in morphological traits are correlated with genetic structure and partly support the recent taxonomic delimitation proposed for the species complex. The species started to diversify in the Pliocene ca. 5 Mya. We detected a phylogeographical break in species distribution into northern and southern clades between the Bocaina region and the southern portion of the Atlantic Forest. Main Conclusions: We identify how geography and environmental changes through time shape floral bracts and leaves in similar ways. At highly seasonal sites with lower annual precipitation (in the southern subtropical portion of the Atlantic Forest), leaves are larger and floral bracts are wide‐elliptic, making them better suited for increased water accumulation. In contrast, at less seasonal sites (in the tropical north, where rainfall is more abundant and temperatures are higher), leaves are narrower and floral bracts are lanceolate‐shaped, facilitating water drainage. The biogeographical break we identified suggests a role of tectonic activity and climatic oscillations in promoting species divergence and diversification.